The effects of test specimen shape tolerances on determining the mechanical and energy dissipation properties of limestone rock (Rudarsko-geološko-naftni zbornik, 2025)
The uniaxial compressive strength (UCS), Young's modulus (E) and Poisson's ratio (ν) of intact rock depend on the cylindrical specimen shape tolerances (flatness of ends R, their parallelism P and perpendicularity to the specimen axis O). Today's specimen acceptance criteria (allowable R/P/O) are based on scarce research data from the 1970s that mostly relate to UCS without considering the rock strength category (worst case scenario). They are also very strict and, in some cases, difficult to implement, requiring engineering judgment. To increase reliability and facilitate judgment of specimen acceptability, this study investigates the influence of shape tolerances on all UCS/E/ν properties and related energy dissipation properties (total, elastic and dissipated energy) for limestone and comparable medium-strength rock with UCS around 100-150 MPa. Ninety specimens were prepared with target (wider) shape tolerances (R up to 0.5 mm; P, O up to 2°) using specially developed equipment for accurate R/P/O determination. These specimens were further tested in uniaxial compression with several relevant measurement settings and all mechanical and energy dissipation properties were determined. From many experimental results and additional statistical/numerical/energy analyses, reliable behaviour models for UCS/E/ν dependence on R/P/O have been established that can be further used to assess the consequences of shape tolerances and specimen acceptability. If limits of natural variability for 'ideal' specimens are applied to these models, critical tolerances that reduce the existing requirements are obtained (e.g. R = 0.08 mm instead of 0.05 mm), which are proposed as supplementary to optimize the testing process for medium-strength rocks.